Electric Fields in the Concept of the Scalar-Vector Potential (Global Journal of Science Frontier Research, 2018)
All dynamic laws of electrodynamics, connected with the motion of charge, follow from the concept of scalar-vector potential. From this concept follow the emission laws. These laws are introduced with the aid of the being late scalar vector potential. This approach gives the possibility to understand physics of the process of emission and to obtain all necessary laws of this process.
Keywords: electrodynamics; electric field; emission laws; scalar- vector potential